KONSEP KESUCIAN IBADAH DALAM QS. AL-BAQARAH AYAT 43; PERSPEKTIF TAFSIR DAN PRAKTIS - Siti Muhibah; Nurhotimah Harahap; Adibah Yasmina Aisha (Yayasan Baitul Hikmah al-Zain, 2025)
The study of the sanctity of worship in the Qur’an has re-emerged as a significant theological and practical discourse within contemporary religious life. This research aims to analyze the concept of worship sanctity as contained in QS. Al-Baqarah verse 43 through classical and contemporary exegetical approaches, as well as its normative and practical implications for religious life. This study employs a library research design with a qualitative–hermeneutic approach. Primary sources include authoritative tafsir works such as Tafsir al-Ṭabari, al-Qurṭubi, Ibn Kathir, and Tafsir al-Misbah, while secondary sources consist of scholarly articles, books, and empirical studies related to the practice of worship. The findings reveal that the sanctity of worship referred to in QS. Al-Baqarah verse 43 not only emphasizes physical purity through ablution, clothing, and the place of worship, but also encompasses spiritual purity reflected in sincerity of intention, adherence to Islamic law, and preservation of moral conduct in social life. Exegetes unanimously affirm that prayer (ṣalāh) represents the most concrete manifestation of worship sanctity, as it simultaneously integrates ritual, ethical, and social dimensions. These findings reinforce that the sanctity of worship has practical implications for the formation of religious character, social integrity, and ethical awareness of the Muslim community. The study concludes that strengthening both the outer and inner dimensions of worship sanctity constitutes an essential foundation for developing a sustainable and contextual religious life within Muslim society.